SAT0139 Maximum Methotrexate Dose Seem To Be An Only Risk Factor for Development of MTX-Associated Lymphoproliferative Disorders. (15th July 2016) - Higuchi, T.; Higuchi, Y.; Fuke, S.; Takagi, T.; Suzuki, D.; Koyama, Y.
Abstract : Background: Since February 2011, an approved Methotrexate (MTX) dose for rheumatoid arthritis: RA treatment has been raised from 8mg/wk to 16mg/wk in Japan. Recently, we have an impression that incidence of MTX-associated lymphoproliferative disorders (MTX-LPD) are increasing. Objectives: To investigate incidence and etiology of MTX-LPD. Methods: All of adult patients receiving MTX for treatment of autoimmune diseases (n=244) in our hospital from May 2012, to August 2015 are surveyed. In each case, the possible risk factors for development of MTX-LPD including minimum MTX dose, maximum MTX dose, administration period, and cumulative dose were investigated in detail. In order to detect the important risk factors, Cox proportional hazards regression analysis (Cox model) were carried out. Results: At baseline, the background of the patients were as follows: male-to-female ratio was 4:3, age was 72.3±8.5 years, minimum MTX dose was 5.4±1.0mg/wk, maximum MTX dose was 10.9±3.6mg/wk, administration period was 274.4±379.7wk, and all cumulative dose was 1842.3±1358.1mg. By the end of 2015, seven of patients developed (six RA, one psoriatic arthritis: PsA). The incidence was accounted for 2.9% in all amenable patients by following up for 119 weeks on average. By Kaplan-Meier plots, incidence of MTX-LPD was 0.85% at up to 52weeks and 9.2% at up to 260weeks. Cox model analysis revealed that maximum MTX dose was the only independent risk factor for MTX-LPD development. The annual incidence of MTX-LPD increases 1.58 times with 1mg increment of MTX (p=0.009, 95%CI 1.12–2.25). The seven MTX-LPD cases include three DLBCL, two indeterminable, and one Hodgkin's lymphoma. The last one had both Follicular and Hodgkin's lesions. The EBV in blood level was significantly elevated in all checked cases, and EBER was positive in six specimens of five cases by histopathological inspection. All of the lymphoproliferative lesions regressed spontaneously after MTX was withdrawn. Conclusions: In our cohort, the incidence of MTX-LPD was quite frequent as compared to previous Japanese report (0.5%; before 2011) or reports from worldwide (0.05–0.3%). It is of particular interest that the annual incidence of MTX-LPD increases 1.58 times with only 1mg increment of MTX a week. It is also notable that all of the lesions regressed spontaneously so far after cessation of MTX, and the connection with EBV infection was found in all investigated cases. Although our cohort is rather small, we believe that it is worth to survey why the incidence of MTX-LPD are increasing in Japan with a larger cohort study. It may reveal the etiology of MTX-LPD in detail. Disclosure of Interest: None declared